2010
DOI: 10.1016/j.pain.2009.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Spinal antinociceptive effects of cyclooxygenase inhibition during inflammation: Involvement of prostaglandins and endocannabinoids

Abstract: Both cyclooxygenase-1 and -2 are expressed in the spinal cord, and the spinal COX product prostaglandin E(2) (PGE(2)) contributes to the generation of central sensitization upon peripheral inflammation. Vice versa spinal COX inhibition is considered an important mechanism of antihyperalgesic pain treatment. Recently, however, COX-2 was shown to be also involved in the metabolism of endocannabinoids. Because endocannabinoids can have analgesic actions it is conceivable that inhibition of spinal COX produces ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 60 publications
4
68
1
3
Order By: Relevance
“…The spinal COX product PGE2 contributes to the generation of central sensitization upon peripheral inflammation (Telleria-Diaz et al, 2010). Given evidence that inhibition of PGE2 release can reduce behavioral signs of pain after SCI (Hains et al, 2001) and peripheral nerve injury (McMahon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The spinal COX product PGE2 contributes to the generation of central sensitization upon peripheral inflammation (Telleria-Diaz et al, 2010). Given evidence that inhibition of PGE2 release can reduce behavioral signs of pain after SCI (Hains et al, 2001) and peripheral nerve injury (McMahon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent report, linking COX-2 inhibition to increased endocannabinoid levels, suggests the ECS and the COX-mediated prostaglandin pathway to be closely connected. 35) In conclusion, it is clear that cannabinoids inhibit COXenzymes, but in a higher concentration range, as compared to anti-inflammatory drugs (i.e. indomethacin).…”
mentioning
confidence: 90%
“…IT pretreatment with AM-251, the selective cannabinoid CB1 receptor antagonist, blocked the analgesic effects of indomethacin and flurbiprofen in animal pain models (22). The inhibition of COX-2 at the spinal cord level decreased both prostaglandin generation and endocannabinoid degradation and indicated that the endocannabinergic mechanisms was more responsible for their antinociceptive activities than the inhibition of spinal prostaglandin synthesis (39). Overall, the possible reaction pathways of celecoxib in this study are shown in Figure 4.…”
Section: Discussionmentioning
confidence: 68%